Catalytic formal cycloadditions between anhydrides and ketones: excellent enantio and diastereocontrol, controllable decarboxylation and the formation of adjacent quaternary stereocentres. Issue 11 (18th February 2016) - Cornaggia, Claudio; Gundala, Sivaji; Manoni, Francesco; Gopalasetty, Nagaraju; Connon, Stephen J.
Abstract : It has been shown for the first time that enolisable anhydrides can participate in highly efficient and diastereo/enantioselective additions to activated ketones. Abstract : It has been shown for the first time that enolisable anhydrides can participate in highly efficient and diastereo/enantioselective additions to activated ketones. In these reactions the anhydride component formally acts (initially) as the nucleophilic component. These processes are promoted by novel, readily prepared urea-substituted cinchona alkaloid-derived catalysts at low loadings under mild conditions. Three classes of enolisable anhydride and three different types of activated ketone were shown to be compatible with the process – generating a diverse range of structurally distinct and densely functionalised lactone products with the formation of two new stereocentres, one of which is quaternary. In one example, a product incorporating two contiguous quaternary stereocentres (one all carbon) was formed with outstanding enantiocontrol. It has been shown in the case of glutaconic anhydride derivatives that the cycloaddtion process is reversible, and can be accompanied by decarboxylation and olefin isomerisation. Reaction conditions can be modified to give access to three types of product with good–excellent ee.